Keterlibatan Orang Tua terhadap Minat Baca Anak - Murtiningsih, Murtiningsih (Dinamika Pendidikan, 2008)
Reading skills is kind oj complex ability which is influenced  by manyfactors. It is motivation/actor,   someone with high motivation and interest on reading are going to have a routine reading activity without being pushed or ordered by anyone else. This/actor will impact the same things on child. Kids with parents  that aware on the importance of reading skills will try to give a chance to their kids to learn how to read and let them get their own motivation on reading. Family is the most perfects  and exact place/or kids to learn reading. Parents support could be much needed to plant reading's motivation to kids and it is their responsibility to fills up kids necessary on every single thing especially to parenting them. Parents are the one who know the exact ways to motivate their kids to reading. Lots of ways that parents  could do to push kid's reading  motivation   such us.' (1) telling story to the kids (2) ask the kids to do words and numbers play (3) give a chance to kids to choose and reads their own choices books (4) Prepare an interesting story books. (5) give a comment to the books that has been read by the kids